Online Public Access Catalogue - Aruna, A. (DESIDOC Journal of Library & Information Technology, 2003)
Developments in stand-alone systems led libraries to use these systems and streamline their data processing operations. Apart from routine operations, the libraries started developing bibliographic databases by inputting the bibliographic details of the books available in the particular library. Now the scenario is that these databases are available on networks. http://dx.doi.org/10.14429/dbit.18.5.3408